2020
DOI: 10.1111/1462-2920.15156
|View full text |Cite
|
Sign up to set email alerts
|

The treatment and follow‐up of ‘recurrence’ with discharged COVID‐19 patients: data from Guizhou, China

Abstract: Summary We reported 20 cases of discharged COVID‐19 patients whose RT‐PCR test results showed ‘re‐positive’. After finding ‘re‐positive’, these patients were admitted to hospital for the second time and were followed up until the end of May 2020. We recorded detailed treatment and follow‐up process, and collected relevant data. The possible causes and potential clinical significance of this phenomenon are discussed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
38
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(38 citation statements)
references
References 19 publications
0
38
0
Order By: Relevance
“…Within the first admission, considering 1064 patients, the majority of re-positive cases ( n = 987; 92.7%) were asymptomatic or had mild to moderate symptoms [ 1 , 3 , 13 , 14 , 16 , 17 , 19 , 21–24 , 26–28 , 30–33 , 36–45 , 47 , 48 , 50–52 , 54 , 56 , 58 , 59 , 61 , 62 , 64–67 , 69–73 , 75 , 77 ], but some of them had severe or critical disease ( n = 77, 7.3%) [ 1 , 13 , 18 , 21 , 23 , 24 , 27 , 30 , 31 , 35 , 36 , 39 , 42 , 43 , 46 , 49 , 55 , 60 , 63 , 68 , 74 ]. To compare the severity of disease during the first and second courses of illness in re-positive patients, 57 studies including 858 re-positive patients, it was reported that the disease severity decreased or remained unchanged in 835 cases (97.3%) [ 13 , 15–20 , 23 , 24 , 26 , 28–31 , 33 , 36–48 , 50 , 52–54 , 58–61 , 65–68 , 70 , 71 , …”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Within the first admission, considering 1064 patients, the majority of re-positive cases ( n = 987; 92.7%) were asymptomatic or had mild to moderate symptoms [ 1 , 3 , 13 , 14 , 16 , 17 , 19 , 21–24 , 26–28 , 30–33 , 36–45 , 47 , 48 , 50–52 , 54 , 56 , 58 , 59 , 61 , 62 , 64–67 , 69–73 , 75 , 77 ], but some of them had severe or critical disease ( n = 77, 7.3%) [ 1 , 13 , 18 , 21 , 23 , 24 , 27 , 30 , 31 , 35 , 36 , 39 , 42 , 43 , 46 , 49 , 55 , 60 , 63 , 68 , 74 ]. To compare the severity of disease during the first and second courses of illness in re-positive patients, 57 studies including 858 re-positive patients, it was reported that the disease severity decreased or remained unchanged in 835 cases (97.3%) [ 13 , 15–20 , 23 , 24 , 26 , 28–31 , 33 , 36–48 , 50 , 52–54 , 58–61 , 65–68 , 70 , 71 , …”
Section: Resultsmentioning
confidence: 99%
“…Different studies observed no significant association between the recurrence susceptibility and the presence of these serum-specific antibodies [ 13 , 14 , 34 ]. Several cases with recurrence have been tested positive for the IgG test [ 31 , 34 , 49 ]. According to this evidence, it could be speculated that antibody presence does not necessarily prevent disease recurrence.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…One of the main purposes of follow-up is to monitor nucleic acid reactivation. Although the current evidences suggest that positivity on follow-up RT-PCR not imply infectivity [22], typical symptoms occur in a significant proportion of recurrence patients and require further treatment [23][24][25]. On the other hand, it is imperative to understand the possible outcome of discharged COVID-19 patients, especially if they have any other detrimental illnesses by longitudinal analysis to safeguard their life in future [26,27].…”
Section: Discussionmentioning
confidence: 97%